Makna Gramatikal dalam Pidato Aksi Akbar Aliansi Rakyat Indonesia Bela Palestina di Monas - Amaliyah, Milah Rizki; Putri, Siti Nabila; Firmansyah, Dodi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Language became an important communication tool for humans. When speaking, of course, there is a meaning contained in each word, both intact and that has undergone a combination or grammatical process. Currently, many media are developing as a means of communication, one of which is YouTube. Youtube has a wide coverage and can access news both at home and abroad. Researchers are interested in making YouTube media about the news that is on the rise, namely "Action Speech of the Indonesian People's Alliance to Defend Palestine" as a semantic study that focuses on grammatical meaning. The purpose of this study is to describe and explain the grammatical meaning in the "Action Speech of the Indonesian People's Alliance to Defend Palestine". This study used qualitative descriptive method. Data collection techniques are carried out by the listen and record method. The results of the analysis showed the grammatical meaning of 121 data which included the affixation of 106 data (prefixes 41 data, suffixes 26 data, and confixes 39 data), reduplication of 12 data and composition or compounding of 2 endocentric composition data and 1 exocentric composition data.